Medytacja nad Pustką. Konteksty buddyjskie w „Końcówce" i „Szczęśliwych dniach” Samuela Becketta - Klimczak, Dariusz Piotr (Przestrzenie Teorii, 2007)
Thanks to Buddhist contexts, present in S. Beckett's two long plays (The Endgame and The Happy Days) we understand that death, signifying the ultimate Nothingness and Emptiness appears to be the change of the perceiving substance, which getting rid of the body, is joined with the nonbodily content of the things. Beckett's doxology of the light makes it that since Life is compared to the flame, Death depicts its extinguishing, but at the same time the value of eschatological hope is expressed through Buddhist motifs (karma of the Yoga, little Buddha, nirvana, the wheel of Samsara and the like). Death is for Winnie, Hamm and Clove an internal act of transgression, touching directly the dying person, but at the same time the heroes of Beckett's plays transfer their feeling connected .with dying to the external observer (the spectator). And so Beckett achieved the dimension of the most important function of the theatre of „participation" and „initiation". Recognising Buddhist contexts in Beckett's plays, we accept Death as one of the stages of the biological cycle - being a peculiar kind of repayment of a debt to nature.